Pengaruh BPA (Bisphenol A) terhadap Kadar Insulin dalam Serum Darah Tikus Wistar Jantan - Fitria Nurhabiba Agustine; Swasthi Prasetyarini; Zahreni Hamzah (Fakultas Kedokteran Gigi Universitas Jember, 2019)
BPA is a synthetic material that widely used in basic material of PVC making. PVC is needed in production of household appliances, food container, mineral water bottles, feeding bottles and dental sealant. BPA is known as one of EDCs which have an effect to increase insulin levels on blood. Furthermore, BPA could lead to DMT2. The objective was to determine the effect of BPA on blood insulin levels in adult male wistar rats. 18 male wistar rats were divided into 3 groups. BPA solution was made by dissolve 20 mg/kgBB crystal BPA into corn oil. Group 1 (K1) not given any treatment and dissected in day-0. Group 2 (K2) given aquadest treatment orally for 28 days and dissected in day-29. Group 3 (P) given BPA solution treatment orally for 28 days and dissected in day-29. The treatment given once a day on 09.00 AM. The blood collected after 12 hours fasting. Blood collecting procedure done with the rats were anasthetized first with eter 10% through inhalation and then dissect the rats until the heart is exposed. Blood was collected from the heart for 3 ml and were sentrifugated to get the serum. Insulin examination done by ELISA on serum that has been collected. Data were analyzed by One Way Anova test and Post hoc Test LSD. BPA with 20 mg/kgBB dose increasing blood serum insulin levels on adult male wistar rats by 1,38 mIU/L.